Given the equation:

3x+4y = 26...........(1)

x - 2y = -8 ............(2)

First we will multiply (2) by 2 :

==> 2x - 4y = -16...........(3)

Now we will add (1) and (3)

==> 5x = 10

==> x = 2

==> Now we will substitute x=2 into (2) to...

## See

This Answer NowStart your **48-hour free trial** to unlock this answer and thousands more. Enjoy eNotes ad-free and cancel anytime.

Already a member? Log in here.

Given the equation:

3x+4y = 26...........(1)

x - 2y = -8 ............(2)

First we will multiply (2) by 2 :

==> 2x - 4y = -16...........(3)

Now we will add (1) and (3)

==> 5x = 10

==> x = 2

==> Now we will substitute x=2 into (2) to find y.

==> x - 2y = -8

==> 2 - 2y = -8

==> -2y = -10

==> y= 5

**Then, the solution to the system is the pair ( 2, 5)**